Avaliação do comportamento de vigas de concreto auto-adensável reforçado com fibras de aço - Barros, Alexandre Rodrigues de (2009)
The self-compacting concrete (SCC) has been characterized as a great evolution in the concrete technology, being able to fill all empty spaces of the formwork and selfcompacting only by action of its own weight. If steel fibers are added to SCC, without prejudice its properties in the fresh state, new advantages and possibilities of applications will provide concretes more efficient. In this context, a SCC with addition of industrial waste is used, and steel fibers with l/d ratio equal to 50 are incorporated, in a volume fraction of 1%, in order to assess the behavior of reinforced self-compacting concrete beams, with and without the addition of steel fibers, subject to normal and tangential stresses, and compare them with the behavior of conventional reinforced concrete beams. For that, were made reinforced concrete beams of dimensions (12,5 x 23,5 x 132) cm, which were tested by four-point bending, to the 28 days of age. To compare the results, were produced conventional concretes of different compositions, with and without steel fibers. The tests results in the fresh state shown that was possible the obtaining of concrete with self-compacting properties, even with the addition of steel fibers, from a mix already existent of SCC. The addition of the steel fibers to the SCC promoted slight gain in the load capacity of the beam, with lower displacements in the middle span, lower deformations in the reinforcement bars and improved cracking control, compared to the others beams produced with concrete compacted by vibration, with and without steel fibers.